Rapid diagnostic tests versus peripheral smear in malaria: a comparative study - Dr Padmaja Kulkarni; Dr Varna I (Tropical Journal of Pathology and Microbiology)
Introduction: Malaria is one of important vector borne disease in India. It can be fatal if not treated promptly. The early diagnosis and treatment of malaria is essential to prevent complications especially in cerebral malaria. Aims: To evaluate the diagnostic accuracy of Rapid Diagnostic tests (RDT) in the diagnosis of malaria. Methods and Material: Blood samples from all clinically suspected cases of malaria were routinely subjected to peripheral smear examination and RDT for the presence of malaria parasite. Statistical analysis used: Sensitivity, Specificity, Positive predictive value and Negative predictive value were analyzed using standard formulae. Results: RDT are having Sensitivity, specificity, Positive Predictive Value and Negative Predictive value of 100%, 96.7%, 92.5% and 100% respectively. Conclusions: RDTs are equally or more sensitive and specific than peripheral smear. Newer Pf /Pv specific antigen RDT kits can distinguish mixed and PF infections. However further studies are required to assess cost effectiveness and efficiency of different RDTs.